Hypertonic saline for severe symptomatic hyponatraemia: real-world findings from the UK. Issue 5 (23rd May 2022) - Arshad, Muhammad Fahad; Iqbal, Ahmed; Weeks, James; Fonseca, Ines; Munir, Alia; Bennet, William
Abstract : Objective: To evaluate 'real-world' safety and efficacy of the European Society of Endocrinology guidelines for the treatment of severe symptomatic hyponatraemia using hypertonic saline (HTS). Design: Retrospective, observational, cohort study, examining the use of HTS for severe symptomatic hyponatraemia at Sheffield Teaching Hospitals between 2017 and 2020. Methods: Patients were identified from pharmacy records and demographic, clinical, and treatment data extracted. Results: Out of 112 patients (females:males = 61:51), the mean age ± s.d. was 66.3± 16.0 years and mean pre-treatment serum sodium ± s.d. was 113.8 ± 6.4 mmol/L. Overall, overcorrection rates at 24 and 48 h (>10 and >18 mmol/L) were 44.9 and 19.6%, respectively, while 19.6% of patients were treated for overcorrection. Above-target rise in sodium (>5 mmol/L) after first and second boluses was noted in 22.6 and 34.6% of patients, respectively. In-hospital and 12-month mortality was 7.1 and 18.7%, respectively, with no cases of osmotic demyelination. The mean venous blood gas (VBG) sodium was 1.9 mmol/L lower than paired serum sodium ( n = 36) (113.6 ± 6.6 vs 115.7 ± 7.8 mmol/L). Conclusion: We report real-world data demonstrating that a significant number of patients overcorrected using current guidelines. Also, several patients had above-target rise in sodium after one bolus of HTS, and sodium measurement should be considered before the second bolus unless ongoing severe symptoms persist. A point of care VBG sodium concentration was useful for this purpose. In addition to careful monitoring, a cautious but anticipatory overcorrection prevention strategy should be considered in the first 24 h.